2003
DOI: 10.1007/s00210-003-0757-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atropine on human cardiac β1- and/ or β2-adrenoceptor stimulation

Abstract: The aim of this study was to find out whether, in humans, the increase in vagal tone accompanying cardiac beta-adrenoceptor (beta-AR) stimulation might be different dependent on beta1- or beta2-AR stimulation. For this purpose we studied, in six male healthy volunteers (aged 28+/-1 years), the effects of atropine infusion (0.15 microg/kg/min continuously) on increase in heart rate (HR) and contractility (determined as shortening of HR-corrected duration of electromechanical systole-QS2c) evoked by infusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…18). Indeed, when cardiac muscarinic tone is acutely blocked with atropine, ␤-adrenergic-mediated increases in heart rate are greater (3,17,31), suggesting a blunting effect of vagal tone on the adrenergic response in the heart. There is little information about the effects of chronic lack of vagal tone on cardiac ␤-adrenergic receptor function.…”
mentioning
confidence: 97%
“…18). Indeed, when cardiac muscarinic tone is acutely blocked with atropine, ␤-adrenergic-mediated increases in heart rate are greater (3,17,31), suggesting a blunting effect of vagal tone on the adrenergic response in the heart. There is little information about the effects of chronic lack of vagal tone on cardiac ␤-adrenergic receptor function.…”
mentioning
confidence: 97%
“…52 The Ile164 variant of the β 2 AR gene in endothelial cells loses the ability to mediate cell specific responses to catecholamine. 53,54 To gain better insight on the role of Ile164 on atherosclerosis, Piscione et al showed that adenoviral (Ad) β 2 AR-Ile164 infection reduces isoproterenol mediated Vascular smooth muscle cells (VSMC) proliferation. 55 In humans, vascular responses and heart contractility are altered in subjects carrying the Ile164 variant of the β 2 AR gene compared with wild-type volunteers.…”
Section: β Adrenergic Receptorsmentioning
confidence: 99%